Antibody functionalized gold nanoparticles for mitochondria targeting and hyperthermia: a proof of concept in colorectal cancer - Gomes, Susana Matilde Carvalho (2022)
Colorectal cancer (CRC) has a high incidence and mortality rate, and traditional cancer therapies are not enough to treat and improve cancer patients' quality of life. Therefore, new therapeutic approaches are being studied, mainly focusing on improving the targeting specificity, not only to cancer cells but also to certain cellular compartments. Mitochondria are a promising target organelle for cancer therapies since they are involved in both cell health (being the cell's engine) and cell death (e.g., apoptosis). Nanomedicine provides effective multifunctional nanocarriers for a range of innovative cancer therapeutic strategies. Gold nanoparticles (AuNPs), due to their high surface area to volume ratio, have specific features that make them a great bet on cancer treatment. Among them, unique optical characteristics and the high capability in surface modifications. It has been shown that using a green laser that triggers an enhanced photothermal conversion by AuNPs this leads to cancer cells’ death. Thus, this work aimed to assess whether targeting mitochondria of cancer cells followed by hyperthermia could improve cancer cell death by destabilizing or disrupting mitochondria. With this purpose, AuNPs were functionalized with a specific antibody against Hexokinase I (anti-Hexokinase I), a protein expressed in the mitochondrial outer membrane (MOM). This new nanoformulation (AuNP@PEG@Anti-Hexokinase I) was successfully synthetized and characterized prior to in vitro assays with a CRC cell line- HCT116. Then, internalization and mitochondrial targeting in HCT116 cells were assessed by complementary techniques, and all together seemed to indicate that AuNP@PEG@Anti-Hexokinase I had specificity for targeting mitochondria. Hyperthermia effect of AuNP@PEG@Anti-Hexokinase I did not have prominent outcomes, however, further studies are required. This study provides an initial step towards modulating mitochondria targeting using nanomedicines towards improved cancer therapies.